Analisis Konfiks Pada Karangan Narasi Siswa Kelas VII SMP Al-Islam Kartasura Tahun Ajaran 2016/2017 - Pristika, Rachma; , Dr. Yakub Nasuha,M.Hum (2017)
Rachma Pristika/A310130059. CONFORT ANALYSIS ON NARRATIVE STUDENTS CLASS VII SMP AL-ISLAM KARTASURA ACADEMIC YEAR 2016/2017. Essay. Faculty of Teacher Training and Eduction, Muhammadiyah University of Surakarta. Juni, 2017. This research includes two interesting issues to be studied can be formulated, 1), How the forms of conflicts on class VII students of SMP Al-Islam Kartosuro academic year 2016/2017?. 2) How is the confiction of the students of class VII of Islamic Junior High School Al-Islam Kartasura academic year 2016/2017 ?. The purpose of the research is 1)describe the forms of confix on the essay of the seventh grade students of SMP Al-Islam Kartasura academic year 2016/2017 and 2) identify the use of confix on the text of the students of the seventh grade of SMP Al-Islam Kartasura academic year 2016/2017. This research uses descriptive qualitative method. Sources of data and in this research is the use of confix on the essay of class VII students of SMP Al-Islam Kartasura. Technique of collecting data used that is refer and record. Technique of data analysis using technique of agih. Test data validity using triangulation technique. The results of this study are (1) The use of confix found in this research has five kinds of confix, namely ke-an, pe-an, per, ber-an, as it is. The use of the 17th confix is 17 words. The use of confix pe-6 words. The use of the corresponding confix is 7 words. The use of a fixed confix contains 1 word. The use of confix has four words. (2) The confixed function found in this study is that there are three word-forming functions of 35 data. The use of confixes can be formed through three basic forms such as adjectives, nouns and verbs.